2014
DOI: 10.7150/ijbs.9297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Olfactory Genes in Chilo suppressalis by Antennal Transcriptome Analysis

Abstract: Antennal olfaction, which is extremely important for insect survival, mediates key behaviors such as host preference, mate choice, and oviposition site selection. In insects, odor detection is mediated by multiple proteins in the antenna, especially the odorant receptors (ORs) and ionotropic receptors (IRs), which ensure the specificity of the olfactory sensory neuron responses. In this study, we identified the olfactory gene repertoire of the rice stem borer, Chilo suppressalis, an economically important agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
123
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 39 publications
20
123
1
Order By: Relevance
“…Compared with insects in which the chemosensory receptor genes were identified by analyzing antenna transcriptomes, the number of the candidate ORs and IRs identified by the current study in A. lepigone was similar to the numbers found in H. armigera (OR:60, IR:21) (Liu et al, 2014a) and H. assulta (OR:51, IR:24) (Xu et al, 2015), but more than that of Chilo suppressalis (OR:47, IR:20) (Cao et al, 2014) and Spodoptera litura (OR:26, IR:9) (Feng et al, 2015).…”
Section: Identification and Phylogenetic Tree Of Candidate Or And Irsupporting
confidence: 54%
“…Compared with insects in which the chemosensory receptor genes were identified by analyzing antenna transcriptomes, the number of the candidate ORs and IRs identified by the current study in A. lepigone was similar to the numbers found in H. armigera (OR:60, IR:21) (Liu et al, 2014a) and H. assulta (OR:51, IR:24) (Xu et al, 2015), but more than that of Chilo suppressalis (OR:47, IR:20) (Cao et al, 2014) and Spodoptera litura (OR:26, IR:9) (Feng et al, 2015).…”
Section: Identification and Phylogenetic Tree Of Candidate Or And Irsupporting
confidence: 54%
“…Consequently, the female-and male-antennal transcriptomes of C. sinica were sequenced in this study. A total of 14 Gb of C. sinica antennae transcriptome data was obtained, which is larger than that from many other insects (Grosse-Wilde et al, 2011;Glaser et al, 2013;Zhang et al, 2013;Cao et al, 2014a;Cao et al, 2014b). After extensive sequencing and assembly, 19 CSPs, 12 OBPs, 36 ORs, and 64 IRs, were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first insect ORs were discovered in the fruit fly (Clyne et al, 1999;Vosshall et al, 1999), multiple homologs have been identified (Robertson and Wanner, 2006;Bohbot et al, 2007;Engsontia et al, 2008;Li et al, 2013b;Zhang et al, 2013;Cao et al, 2014b). ORs play a key role in detecting odorants and triggering the transduction of chemical signals to electric signals (Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequence alignment was performed using CLUSTALX [30]. For the phylogenetic analysis, the amino acid sequences of Drosophila melanogaster [31, 32], H. armigera [33], M. sexta [34], Ostrinia furnacalis [35, 36], Chilo suppressalis [37], B. mori [19, 38], S. litura [23], and Heliothis virescens [39] were used. Phylogenetic analyses were conducted using the maximum likelihood method of MEGA 6.0, which was based on the Jones-Taylor-Thornton substitution model, partial deletion gaps with 95% site coverage cutoff, and nearest neighbor interchanges heuristic search [40].…”
Section: Methodsmentioning
confidence: 99%